How to Develop 21st Century Skills in Students: The Role of LEGO Education - Zhou, Longjun (Science Insights Education Frontiers, 2023)
The concept of “21st century skills” emerged in response to the challenges of the modern era. The Partnership for 21st Century Skills (P21) was a pioneering force in this movement and developed the Framework for 21st Century Learning in the early 2000s (Shi et al., 2016). In 2012, the U.S. National Research Council issued a report titled Education for Life and Work: Developing Transferable Knowledge and Skills in the 21st Century, which marked a new direction for educational reform and development in the U.S. and provided valuable insights for nations worldwide. The report identified three domains of competence that comprise 21st century skills: cognitive, intrapersonal, and interpersonal. Each domain consists of several clusters of relevant competencies. The cognitive domain includes cognitive processes and strategies, knowledge, and creativity. The intrapersonal domain encompasses intellectual openness, work ethic/conscientiousness, and positive core self-evaluation. The interpersonal domain is divided into two clusters: teamwork and collaboration, and leadership (National Research Council, 2012). Developing these skills is not only crucial for personal growth and achievement, but also essential for the progress of society as a whole. Therefore, individuals and educational institutions should prioritize the cultivation of 21st century skills in today’s rapidly evolving social and economic environment.